Resilience of savanna forest after clear-cutting in the cerrado-amazon transition zone - Matias Reis, Simone; Schwantes Marimon, Beatriz; Marimon-Junior, Ben Hur; Gomes, Letícia; Morandi, Paulo Sérgio; Galindo Freire, Edson; Lenza, Eddie (Bioscience journal, 2015)
The dynamics of the natural process of recuperation of the structure and diversity of native vegetation following anthropogenic disturbance has been the subject of a great deal of controversy in restoration ecology research. The present study evaluates the natural regeneration of savanna forest (cerradão) 32 and 36 years after the clear-cutting of the vegetation. We compared species diversity, and the structure and dynamics of the vegetation in two communities, one representing preserved cerradão (PC), and the other, the regenerating cerradão (RC), which was clear-cut in 1976. Surveys were conducted in 2008 and 2012, 32 and 36 years after clear-cutting, respectively. In 2008, we demarcated 81 permanent 10 m x 10 m plots, 50 in the RC and 31 in the PC, and measured all live plants with a diameter at soil level > 5 cm. In 2012, the plots were resampled, including the original plants and all the recruits. The species were classified as specialists in savanna (SA) or forest habitat (FO), or as generalists (SA/FO). The RC presented the highest species richness and diversity, density, annual increment, and mortality rates. However, no significant differences were found between communities in the distribution of specialist or generalist species, or between years (2008 and 2012) in basal area or recruitment rates. While the species composition of the two communities is highly similar, the RC was characterized by a higher frequency of SA species, and was more similar to nearby savanna communities (cerrado sensu stricto). Trees in the RC were smaller and suffered higher rates of mortality than those in the PC, but also higher annual increments. While the RC demonstrated a high degree of resilience following clear-cutting, it was still found to be at an intermediate stage of succession, even after almost four decades, indicating that regeneration is a slow process.